2022
DOI: 10.1177/23333928221074895
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Anesthetic Medical Evaluations: Criteria Considerations for Telemedicine Alternatives to Face to Face Visits

Abstract: Background The number of pre-anesthetic medical evaluations (PAMEs) being conducted in primary care is increasing. Due to the COVID-19 pandemic, the use of telemedicine has surged, providing a feasible way to conduct some of these visits. This study aimed to identify patient-related factors where a face to face (FTF) evaluation is indicated, measured by the need for pre-operative testing. Methods A retrospective chart review was conducted on patients age ≥ 18 years who had a PAME between January 2019–June 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Our results align with similar satisfaction rates reported in reviews. [ 6 7 8 9 10 11 12 ] Positive feedback from previous pilot studies further supports patient and anaesthetist satisfaction with telemedicine consultations. [ 7 13 ] In our study, 95% of anaesthetists expressed satisfaction with the quality of teleconsultation.…”
Section: Discussionmentioning
confidence: 91%
“…Our results align with similar satisfaction rates reported in reviews. [ 6 7 8 9 10 11 12 ] Positive feedback from previous pilot studies further supports patient and anaesthetist satisfaction with telemedicine consultations. [ 7 13 ] In our study, 95% of anaesthetists expressed satisfaction with the quality of teleconsultation.…”
Section: Discussionmentioning
confidence: 91%
“…The authors conclude that those without these risk factors could be safely scheduled for a virtual visit. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Even with the implementation of remote consultations, there will still be a group of patients who would benefit from FTF visits. Khera et al [19] identified patient-related factors that determine whether an FTF consultation was indicated. In their study, these factors included patient age above 65 years, presence of type I or II diabetes mellitus, and the use of 7 or more of the listed medications.…”
Section: Remote Consultationmentioning
confidence: 99%